2003
DOI: 10.4049/jimmunol.171.4.2090
|View full text |Cite
|
Sign up to set email alerts
|

Synergism Between Platelet-Activating Factor-Like Phospholipids and Peroxisome Proliferator-Activated Receptor γ Agonists Generated During Low Density Lipoprotein Oxidation That Induces Lipid Body Formation in Leukocytes

Abstract: Oxidized low density lipoprotein (LDL) has an important proinflammatory role in atherogenesis. In this study, we investigated the ability of oxidized LDL (oxLDL) and its phospholipid components to induce lipid body formation in leukocytes. Incubation of mouse peritoneal macrophages with oxidized, but not with native LDL led to lipid body formation within 1 h. This was blocked by platelet-activating factor (PAF) receptor antagonists or by preincubation of oxLDL with rPAF acetylhydrolase. HPLC fractions of phosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0
2

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 56 publications
0
34
0
2
Order By: Relevance
“…40,82 Macrophage lipid bodies, which are formed by different stimuli and pathological conditions including obesity-induced inflammation, ox-LDL-and LPS-induced inflammation or bacterial infection, are increasingly recognized as organelles with key roles in inflammation. [83][84][85][86][87][88] Under inflammatory conditions, they compartmentalize MAP kinases, cPLA 2 , eicosanoid-forming enzymes and are involved in the enhanced eicosanoid synthesis. [84][85][86][87][88][89] In addition, human colon adenocarcinoma cell lines and colon cancer biopsies from patients have recently been shown to exhibit a drastic increase in ADRP and COX-2-enriched lipid bodies.…”
Section: Leptin and Mtor: Partners In Macrophage Metabolism And Activmentioning
confidence: 99%
“…40,82 Macrophage lipid bodies, which are formed by different stimuli and pathological conditions including obesity-induced inflammation, ox-LDL-and LPS-induced inflammation or bacterial infection, are increasingly recognized as organelles with key roles in inflammation. [83][84][85][86][87][88] Under inflammatory conditions, they compartmentalize MAP kinases, cPLA 2 , eicosanoid-forming enzymes and are involved in the enhanced eicosanoid synthesis. [84][85][86][87][88][89] In addition, human colon adenocarcinoma cell lines and colon cancer biopsies from patients have recently been shown to exhibit a drastic increase in ADRP and COX-2-enriched lipid bodies.…”
Section: Leptin and Mtor: Partners In Macrophage Metabolism And Activmentioning
confidence: 99%
“…Indeed, stimuli known to prime leukocytes to induce eicosanoid generation, including PKC activators, arachidonate and PAF, are also active in stimulating lipid body formation. Accordingly, others and we observed a significant correlation between lipid body formation and enhanced generation of both LO-and COX- derived eicosanoids in vitro (Bozza et al 1996a, b, 1997, Bartmenes et al 1999 as well as in vivo , Silva et al 2002, de Assis et al 2003. Analogously, agents that inhibited lipid body formation also resulted in inhibited priming for eicosanoid production.…”
Section: Involvement Of Lipid Bodies In Enhanced Generationmentioning
confidence: 63%
“…Indeed, we observed that treatment of mouse macrophages with BRL 49653, a preferential PPARγ ligand, failed to induce lipid body formation. However, BRL 49653 treatment significantly potentiated lipid body formation induced by ox-LDL or PAF-like agonists, suggesting that PPAR have a role in regulating leukocyte lipid body formation (de Assis et al 2003). However, we anticipate that differences in PPAR expression and role in lipid body formation may vary according to the cell type and stimuli studied and further studies are needed to characterize the roles of PPAR in lipid body formation and the involvement of PPAR targeted genes in this phenomenon.…”
Section: Mechanisms Of Leukocyte Lipid Body Formationmentioning
confidence: 95%
See 2 more Smart Citations